Learning and teaching of fluent musical note recognition: the visual perceptual perspective - Wong, Yetta Kwailing; Fang, Jiaqi Fion (Frontiers in Cognition, 2025)
Musical notation enables communications between composers, performers, music learners and music lovers. However, learning and teaching of fluent musical note recognition is often thought to be highly challenging. This paper aimed to summarize the current understanding of development of musical note recognition, explain its pedagogical bottleneck, and propose a pedagogical tool to address this problem. Review of the psychology and neuroscience literature identified eight psychological factors associated with fluent recognition of musical notes at both behavioral and neural levels. Many of the identified factors involve specialized visual perceptual mechanisms that are automatic, implicit and without conscious effort. Since classroom teaching heavily relies on verbal explanation, which cannot efficiently address these visual perceptual mechanisms, musical note recognition becomes difficult to teach and learn. We propose that visual perceptual training can serve as an innovative pedagogical tool to efficiently relax the visual bottleneck and enhance fluency in recognizing musical notes. We discuss why theoretically it works, the empirical basis for its effectiveness, its advantages, and potential concerns of adopting this tool by the music education community. In sum, visual perceptual training can directly facilitate development of fluency in recognizing musical notes in an efficient and personalized manner. This will encourage music exposure, learning and participation, and may therefore widely benefit the music learning community.